Child protein score as an indicator of stunting risks - Antun Rahmadi; RR. Ratnasari Dyah Purnomowati (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Stunting remains a major nutritional problem in Indonesia, with a prevalence of 19.8%. One of the key determinants of linear growth in young children is protein quality; however, dietary assessments have largely focused on intake quantity or food diversity, while the biological quality of protein is rarely considered. Purpose: To develop and validate the Toddler Food Protein Score (TFPS) as a practical instrument for assessing protein quality and examining its association with stunting risk. Methods: A cross-sectional study was conducted among 109 children aged 6–59 months attending primary health centers, recruited through consecutive sampling. The sample consisted of 49 stunted and 60 non-stunted children. Stunting status was determined using height-for-age z-scores, while protein quality was assessed using the TFPS derived from a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Data analysis included chi-square tests, logistic regression, and ROC curve analysis. Results: The prevalence of stunting was 44.9%, and TFPS scores were significantly lower among stunted children than non-stunted children (2.4 ± 1.1 vs. 3.9 ± 1.2; p < 0.001). ROC analysis yielded an AUC of 0.79 (95% CI: 0.71–0.87; p < 0.001) with a cut-off ≤3. Multivariate logistic regression showed that children with TFPS ≤3 had a 3.3-fold higher risk of stunting (OR = 3.30; 95% CI: 1.50–7.50; p = 0.004). Conclusion: The TFPS is a valid, discriminative, and practical tool that has potential for use as a stunting risk screening instrument in primary healthcare settings.